Literature Review: Cancers Among Workers Exposed To Perfluorooctane Sulfonate (PFOS) - Felicia Erika Jahja; Muhammad Ilyas (ILUNI MKK FKUI and PRODI MKK FKUI, 2022)
Introduction: Cancer is a disease with a high mortality rate in Indonesia. One of the chemical exposures that can cause cancer is perfluorooctanesulfonyl fluoride/perfluoro octane sulphonate (PFOS). PFOS is a chemical that is widely used due to its diverse functions, including use in fire extinguishers, waterproof materials in food boxes and furniture, and household hygiene products. Long-term exposure to workers affected by PFOS is suspected to be one of the risk factors for cancer. Methods: The author conducted a literature search of online search engines in 3 sources PubMed, Google Scholar, and JSTOR databases. The inclusion criteria in this study are articles in English, full text available, and conducted on the working population. The author has not restricted search within the last 5 years due to the limited reference of the topic. Results: Out of a total of 5 articles examined, the authors found the incidence of bladder cancer in workers as much as 1.28 times, there was even a death rate of 12.77 times in workers with PFOS exposure due to bladder cancer, although the results did not statistically significantly. Other studies have shown increased levels of PFOS in the blood but were not associated with changes in other laboratory examinations associated with health problems in workers. Conclusions: The results of the literature study found no significant association in cancer occurrence based on the length of PFOS exposure in workers. The literature search results also found no direct association between PFOS exposure to possible health problems.